2021
DOI: 10.1002/int.22376
|View full text |Cite
|
Sign up to set email alerts
|

Axiomatization and construction of orness measures for aggregation functions

Abstract: The notion of an orness measure for aggregation functions has been a relevant study subject whose history can be traced back to the early works of Dujmović in 1973. Intuitively, an orness measure quantifies the similarity of an aggregation function to the “or” function and results in an essential tool for decision engineering, field in which the choice of aggregation function is sometimes restricted to a desired value of orness (orness‐directed aggregation). In 1988, Yager presented a particular example of orn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For instance, Zhou et al [1], Kukkonen and Deb [2], Pinto-Varela et al [3], Lath et al [4], Pereyra et al [5], Garg [6], Futrell et al [7], Hirpa et al [8], Liu et al [9], Wang et al [10], Cheraghalipour et al [11], Ho-Huu et al [12], Yeh [13], Liu et al [14], Nagamanjula and Pethalakshmi [15], Xu et al [16], Diao et al [17], Mohammadi et al [18], Kparib et al [19], Kparib et al [20], Gulben and Orhan [21], Zaninudin and Paputungan [22], and Stutzle and Hoos [23]. Studies proposing multi-objective optimization techniques and solution can be found in Messac [24], Das and Dennis [25], Deb [26], Messac et al [27], Messac and Mattson [28], Kim and Weck [29], Zhang and Li [30], Chinchuluun and Pardalos [31], Mueller-Gritschneder et al [32], Pereyra et al [5], Pérez-Fernández et al [33], Marler and Arora [34], Gunantara [35], Orths et al [36], Collette and Siarry [37], Ehrgott [38], Eskelinen et al [39], Fonseca and Fleming [40], Alaa et al [41], Subhamoy and Sugata…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zhou et al [1], Kukkonen and Deb [2], Pinto-Varela et al [3], Lath et al [4], Pereyra et al [5], Garg [6], Futrell et al [7], Hirpa et al [8], Liu et al [9], Wang et al [10], Cheraghalipour et al [11], Ho-Huu et al [12], Yeh [13], Liu et al [14], Nagamanjula and Pethalakshmi [15], Xu et al [16], Diao et al [17], Mohammadi et al [18], Kparib et al [19], Kparib et al [20], Gulben and Orhan [21], Zaninudin and Paputungan [22], and Stutzle and Hoos [23]. Studies proposing multi-objective optimization techniques and solution can be found in Messac [24], Das and Dennis [25], Deb [26], Messac et al [27], Messac and Mattson [28], Kim and Weck [29], Zhang and Li [30], Chinchuluun and Pardalos [31], Mueller-Gritschneder et al [32], Pereyra et al [5], Pérez-Fernández et al [33], Marler and Arora [34], Gunantara [35], Orths et al [36], Collette and Siarry [37], Ehrgott [38], Eskelinen et al [39], Fonseca and Fleming [40], Alaa et al [41], Subhamoy and Sugata…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, fuzzy measure, defined by Sugeno in 1974, can be utilized to depict the correlations of attribute indexes [7][8][9][10]. Meanwhile, aggregation functions and aggregation operators are investigated by many researchers recently [11][12][13][14]. Because of the fuzziness and uncertainty of actual decision issues, the evaluation values involved in the decision process are not always expressed as crisp numbers.…”
Section: Introductionmentioning
confidence: 99%